(3GdEbdjOs - (3CMeO Hf eMehO Hf YeQ Hf bGSe, TQa GdOjf GdLfOj,J (B700 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3GdeOQSI GdNGQLjI HCfWGcjI s)
(3ChdgG (B:s
(3hZjQ GdeHge GMJQGR Hg Yf GdeHge aEfg dG jchf ajg eG PcQg ef GdMcejf s
(3BNQgG (B:s
(3bGd eDda gPG GdcJGH GdLfOj gPG eG SHb Hg hYOj ef Cf CaJM GdZdb hddfGS ajeG jYTbhf ePGgH adfNJe s
(3GfXQ GdLRA GdChd (B17 (3fMhs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs